(E)‐β‐farnesene synthase gene affects aphid behavior in transgenic Medicago sativa. Issue 3 (28th September 2018) - Wang, Xuemin; Gao, Yuhao; Chen, Zhihong; Li, Jindong; Huang, Jianping; Cao, Jiangbo; Cui, Miaomiao; Ban, Liping
Abstract: BACKGROUND: Pea aphid ( Acyrthosiphon pisum Harris) is one of the major pests in alfalfa crops, causing significant yield losses. (E)‐β‐farnesene (EβF), an alarm pheromone released by pea aphid, is generic to many species of aphids, and is used to minimize potential danger from predators and parasitoids by avoiding the source of the pheromone. RESULTS: In this study, EβF synthase gene was constructed into a plant expression vector, and overexpressed in alfalfa ( Medicago sativa L.), with expression among transgenic lines confirmed by qRT‐PCR. Subcellular localization analysis showed that EβF synthase gene was expressed in the plasma membrane and nucleus of the leaf. GC/MS of extraction from transgenic alfalfa indicated emission of EβF ranging from 5.92 to 13.09 ng day −1 g −1 fresh tissue. Behavior assays in Y‐olfactometers demonstrated that transgenic alfalfa expressing AaEβF gene could repel pea aphids, with aphids taking a significantly longer time to select a transgenic line compared with the control line ( P < 0.01). CONCLUSION: We have demonstrated a potentially valuable strategy of using EβF synthase genes for aphid control in alfalfa. © 2018 Society of Chemical Industry Abstract : This study explored that the ectopic expression of AaEβF induced the emission of (E)‐β‐farnesene in alfalfa. The emission affected the aphid behavior and repelled pea aphids from the transgenic alfalfa plants.